Ultrahigh tensile strength achieved in a lightweight medium Mn steel via prominent work hardening. (10th May 2023) - Hu, Bin; Shen, Guohui; Wang, Zheng; Li, Shilei; Wang, Yandong; Luo, Haiwen
Highlights: We develop a new ultrastrong low-density steel that can be strain hardened to 2.1 GPa tensile strength and 16% total elongation. The trade-off of strength-ductility-density overcome by tri-phase microstructures: oriented δ-ferrite lamellas and ultrafine austenite (γ) grains both dispersed in martensitic matrix (α'). Gradual release of residual compressive stress, dislocation multiplication and successive γ-to-α' transformation all contribute to prominent work hardening. Abstract: We develop a new ultrastrong medium Mn steel with a density reduced to 7.39 g cm –3 . It has a novel tri-phase microstructure comprising a hierarchical martensitic matrix (α'), dispersed ultra-fine-retained austenite grains (γ), and both compressed and {200} oriented δ-ferrite lamellas, the latter's formation is due to the alloying of high Al and Si contents for reducing density. As a result, both ultrahigh ultimate tensile strength of 2.1 GPa and good ductility of 16% are achieved after an extraordinary plastic strain hardening increment of about 1.4 GPa. The in-situ synchrotron-based high-energy (HE) X-ray diffraction (XRD) examinations during the tensile deformation revealed that the initial presence of residual compressive stress in δ-ferrite could increase the stress required to initiate the plastic tensile deformation of the specimen, leading to the isolated δ-ferrite lamellas mostly deformed elastically to coordinate the plastic deformation of the martensitic matrix during yielding. During the plastic deformation, the gradual release of residual compressive stress in δ and α', the dislocation multiplication in all the three phases and the successive γ-to-α' transformation all contribute to such a prominent work hardening increment. This study facilitates the development of novel strategies for fabricating ultrastrong but light steels. Graphical abstract: Image, graphical abstract